LEGAL REVIEW OF THE DEVELOPMENT OF E-COMMERCE AS AN ELECTRONIC TRADING MEDIA IN INDONESIA - Nurul Hajjan; Lusia Sulastri (Justisi: Jurnal Ilmu Hukum, 2026)
E-Commerce is a new concept that is commonly described as the process of buying and selling goods or services on the Word Wide Web Internet or the process of buying and selling or exchanging products, services and information through information networks including the internet. E-commerce is a business activity that is carried out electronically through an internet network or the activity of buying and selling goods or services through digital communication channels. E- Commerce is doing business online. The existence of E-Commerce is a promising business alternative to be implemented at this time, because E-Commerce provides a lot of convenience for both parties, both from the seller (merchant) and from the buyer (buyer) in conducting trade transactions, even though the parties are on two different continents though. In this research, the method used is the normative legal method with the specifications of the research results used, namely deduction. The purpose of this research is to understand the development of commerce as a trading medium in Indonesia. For e-commerce entrepreneurs, it is necessary to build trust that starts from the reliability of the service system. For consumers, it is necessary not to worry anymore about shopping on the internet. Before buying, you also need to read carefully the existing policies and need to pay attention to whether there is a security system